2017
DOI: 10.1155/2017/1236329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fractional Differential on Correlation Coefficient between EC1:5 and Reflectance Spectra of Saline Soil

Abstract: Soil salinization is one of the most serious environmental issues in arid and semiarid area with severe social, economic, and ecological problems. At present, most inversion models are based on raw reflectance spectra or integer differential transform. In this study, we measured the hyperspectral reflectance and EC 1:5 of soil samples collected form Ebinur Lake to analyze the influence of fractional differential on correlation coefficient between EC 1:5 and reflectance spectra. The results showed that the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This is mainly because in these applications, the fractional-order model has more accurate results than the original integer differential model. FD mainly has three forms of expressions [8,9]: Riemann-Liouville (R-L), Grünwald- Journal of Sensors Letnikov (G-L), and Caputo. Of which, the generally G-L FD can be defined as…”
Section: Comparison Of Fractional Differential and Integermentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because in these applications, the fractional-order model has more accurate results than the original integer differential model. FD mainly has three forms of expressions [8,9]: Riemann-Liouville (R-L), Grünwald- Journal of Sensors Letnikov (G-L), and Caputo. Of which, the generally G-L FD can be defined as…”
Section: Comparison Of Fractional Differential and Integermentioning
confidence: 99%
“…Also, this novel pretreatment method for saline soils could prevent the loss of important information caused by only considering the traditional integer order. Xia et al [9] took the 43 saline soil samples of Ebinur Lake in Xinjiang, China, as data sources, and analyzed the correlation between original spectral reflectance and electrical conductivity. Results showed that fractional derivate could improve the CC for some single bands, such as 505 nm, 2239 nm, and 2443 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pretreatment of hyperspectral signals for saline soil between spectral reflectance and salt content, fractional derivatives can also be used to pretreat other types of soil hyperspectral signals between spectral reflectance and nutrient content. For example, Xia et al [32] used fractional derivative to preprocess the spectrum collected in Ebinur Lake of Xinjiang, China, and the correlation coefficient between electricity conductivity and soil reflectance spectra was analyzed. Results show that fractional derivative details the varying trends of soil reflectance spectra among 0-order to 2-order.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [27] studied the application of fractional-order derivative in the hyperspectral detection of chromium content in desert soil and revealed that 1.8-order derivative model was much better than others. Xia et al [28] studied the soil salinization in Ebinur Lake and proposed a new method to analyze the correlation coefficient between EC 1:5 and spectrum using fractional differential. Results showed that fractional differential mined more hidden details of the spectra.…”
Section: Introductionmentioning
confidence: 99%